2017
DOI: 10.1021/jacs.7b05894
|View full text |Cite
|
Sign up to set email alerts
|

Boron Switch for Selectivity of Catalytic Dehydrogenation on Size-Selected Pt Clusters on Al2O3

Abstract: Size--selected supported clusters of transition metals can be remarkable and highly tunable catalysts. A par--ticular example is Pt clusters deposited on alumina, which have been shown to dehydrogenate hydrocarbons in a size--specific manner. 1 Pt 7 , of the three sizes studied, is the most active and therefore like many other catalysts, deactivates by coking during reactions in hydrocarbon--rich environments. Using a combination of experiment and theory, we show that nano--alloying Pt 7 with boron modifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
198
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 117 publications
(204 citation statements)
references
References 64 publications
4
198
0
Order By: Relevance
“…However, in one exhaustive study we showed that at least for Pt clusters on α‐alumina, the cluster isomerization is highly facile, and all of ∼30 low‐energy minima are indeed easily visited by the system in under 1 ns . Furthermore, since we introduced the Boltzmann ensemble approach, we successfully used it to describe a number of cluster catalyst properties, such as sintering on the support, size‐specific catalytic activity, and composition‐dependent selectivity, in agreement with experiment when it was available . In the case of Pd on UNCD, we note that the global minimum may constitute only circa 43–46 % of the population, depending on the reaction step (see Figure , ∼43 % for global minimum of adsorbed C 6 H 12 ; ∼46 % for adsorbed C 6 H 10 ).…”
Section: Computational Sectionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, in one exhaustive study we showed that at least for Pt clusters on α‐alumina, the cluster isomerization is highly facile, and all of ∼30 low‐energy minima are indeed easily visited by the system in under 1 ns . Furthermore, since we introduced the Boltzmann ensemble approach, we successfully used it to describe a number of cluster catalyst properties, such as sintering on the support, size‐specific catalytic activity, and composition‐dependent selectivity, in agreement with experiment when it was available . In the case of Pd on UNCD, we note that the global minimum may constitute only circa 43–46 % of the population, depending on the reaction step (see Figure , ∼43 % for global minimum of adsorbed C 6 H 12 ; ∼46 % for adsorbed C 6 H 10 ).…”
Section: Computational Sectionsupporting
confidence: 60%
“…Therefore, the global minimum alone cannot accurately represent the catalyst. Less stable isomers are likely to be more chemically reactive and therefore cannot be ignored . In Table , we specify the number of thermally‐relevant isomers of supported clusters and the average charges on the metal atoms.…”
Section: Computational Sectionmentioning
confidence: 99%
“…Next, following our theoretical proposal that dehydrogenation can be made more selective by adding some boron to Pt, experiment was done and confirmed the effect . In calculations, the global minimum of Pt 7 B on Al 2 O 3 has in fact greater affinity to carbon than does the pure Pt 7 on Al 2 O 3 .…”
Section: Ensemble Representation Of Cluster Catalystsmentioning
confidence: 82%
“…Significant amount of work has been devoted so far for the proposal of relevant dispersed monometallic Pt/Al 2 O 3 models, particularly in the case of the gamma polymorph of alumina . The ductility of small platinum clusters (typically, Pt 13 ) appears to be very strong, in the presence of hydrogen, oxygen and hydrocarbons despite the interaction with a support. Moreover, it was shown that Pt 13 clusters exhibit a higher adsorption capacity than the infinite Pt(111) surface .…”
Section: Introductionmentioning
confidence: 99%